Energy efficient laser beam welding of metals with a ultra-high brightness direct-diode laser system - Laukart, Artur; Dobler, Michael; Kohl, Stefanie; Fritsche, Haro; Grohe, Andreas; Kruschke, Bastian; Schmidt, Michael (Energy Efficiency in Strategy of Sustainable Production, 2015)
The rising level of automation in the automotive industry also involves the use of more and more machines and with that an increase in power consumption. This requires the employment of more efficient production processes with higher efficiency. Laser beam welding offers the opportunity to substitute conventional laser sources like solid state lasers with ultra-high brightness direct-diode laser systems which have the advantage of less power consumption at a comparable beam quality. However, the absorption of laser radiation on metallic surfaces depends on the wavelength, thus the effect of the direct-diode laser wavelength on the welding process has to be investigated. In our research the effect of the laser wavelength on energy efficiency was studied by means of numerical simulations. Furthermore, experimental investigations were carried out to validate the numerical solutions. Different aluminum alloys and steel materials which are used in the automotive environment were investigated within the experiments. Due to the current lack of direct-diode laser systems with a laser power comparable to conventional laser systems, numerical simulations were also used to analyze these future systems. Thus we were able to assess the increase of efficiency in laser beam welding which will be achievable with future high-power direct-diode laser systems.
Keywords: laser beam welding; ultra-high brightness direct diode laser; high beam quality; numerical simulation; process modeling; automotive; energy efficiency

Experimental and Numerical Investigations of Laser Beam Welding with an Ultra-high Brightness Direct-diode Laser - Laukart, Artur; Kohl, Stefanie; Fritsche, Haro; Grohe, Andreas; Kruschke, Bastian; Schmidt, Michael (Physics Procedia, 2016)
Laser beam welding of steel sheets with conventional disc and fibre lasers is part of many manufacturing processes, e.g. car manufacturing. In modern times, all manufacturing processes are also evaluated regarding sustainability. Although conventional beam sources have an ever increasing efficiency, direct-diode lasers are said to make a step in the wall-plug efficiency in comparison to conventional beam sources due to a missing brightness-converter. Investigations concerning laser beam welding with ultra-high brightness direct-diode lasers were carried out, showing heat conduction welding as well as deep penetration welding of 22MnB5 steel sheets is possible. Furthermore a beam parameter product of about 8 mm-mrad was measured, showing comparable beam quality to conventional disc and fibre lasers. Metallographic cuts were used for determining the welding penetration depth and cross-section. Especially the cross-sections, as a measure for process efficiency, show almost the same result using a direct-diode laser or a disc laser. Due to the limited laser power of 500W, numerical simulations were used to extend the experimental result
Keywords: Laser beam welding; direct-diode laser; process modeling; process efficiency

Shear-induced incipient motion of a single sphere on uniform substrates at low particle Reynolds numbers - Rodríguez Agudo, José; Illigmann, Christian; Luzi, Giovanni; Laukart, Artur; Delgado, Antonio; Wierschem, Andreas (Journal of Fluid Mechanics, 2017)